2011
DOI: 10.1177/0959683610385725
|View full text |Cite
|
Sign up to set email alerts
|

Holocene history of Lac des Lauzons (2180 m a.s.l.), reconstructed from multiproxy analyses of Coleoptera, plant macroremains and pollen (Hautes-Alpes, France)

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…The average annual temperature in our study area varies between 4 and 6 °C and mean annual precipitation amounts to 1500–2000 mm (Ponel et al . ).…”
Section: Study Area and Previous Workmentioning
confidence: 97%
“…The average annual temperature in our study area varies between 4 and 6 °C and mean annual precipitation amounts to 1500–2000 mm (Ponel et al . ).…”
Section: Study Area and Previous Workmentioning
confidence: 97%
“…Based on pollen data ( de Beaulieu, 1977;Ortu, 2002), a preliminary estimation would be c. 10 ka. In the Inner French Alps, macrofossils, charcoals and pollen records (Ali et al, 2005;Blarquez et al, 2009;Ponel et al, 2011) indicate an establishment between 9 ka and 8 ka, though earlier scattered macrofossils point to an earlier presence of Larix in the Vanoise Massif (Lac du Loup, 2035 m a.s.l., Blarquez et al 2009). In the central Eastern Alps, records covering the early Holocene are scarce.…”
Section: Holocene (Since C 117 Ka)mentioning
confidence: 97%
“…Palaeoentomological studies have already demonstrated that insect remains in a deposit are not necessarily related to the immediate surrounding area (Kenward, 1975(Kenward, , 1976, that insect macrofossils could undergo important taphonomical problems (Kenward, 1976;Ponel et al, 2011) and that deposition of dead beetles from far-afield by wind and water could lead to the formation of complex fossil assemblages, difficult to interpret (Ponel and Richoux, 1997). Beetle taxa were regularly represented by a single occurrence in the sediment core CAVA-1.…”
Section: The Palaeoenvironment History Of Cavallo Island Inferred Fromentioning
confidence: 99%
“…5), could correspond to an early presence of domestic cattle 2500 years before the first archaeological evidence of human presence in the Lavezzi archipelago. Co-occurrences of these bio-indicators have often been used as markers of pastoralism but it is necessary to interpret dung beetle fossils carefully: these specialized insects could be associated with domestic mammals and pastoralism but they could also reveal the local presence of wild animals as shown in the Alps (Lemdahl 2000;Ponel et al, 2001Ponel et al, , 2011 cal. yr B.P.)…”
Section: An Early Human Imprint Inferred From Beetles?mentioning
confidence: 99%
See 1 more Smart Citation